2018
DOI: 10.1016/j.jfma.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength rather than muscle mass is associated with osteoporosis in older Chinese adults

Abstract: Based on our study, muscle strength rather than muscle mass is negatively associated with OS in older people; thus, we should pay more attention to muscle strength training in the early stage of the OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 39 publications
2
26
2
Order By: Relevance
“…However, the majority of participants in that study were women. Conversely to the previously mentioned ndings, one cross-sectional study in China found no differences between skeletal muscle mass index in older adults and T-score [27]. It should be noted that in this study,BMD was not measured by the DXA, but by the quantitative ultrasound at calcaneus.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, the majority of participants in that study were women. Conversely to the previously mentioned ndings, one cross-sectional study in China found no differences between skeletal muscle mass index in older adults and T-score [27]. It should be noted that in this study,BMD was not measured by the DXA, but by the quantitative ultrasound at calcaneus.…”
Section: Discussioncontrasting
confidence: 93%
“…Femoral neck and hip BMD and T-score as well as whole body T-score and BMC were correlated with handgrip strength. In older Chinese adults, higher handgrip strength was associated with lower risk of osteoporosis [27]. Although, in older Chinese women with osteoporosis, handgrip strength was correlated with femoral neck, hip and lumbar spine BMD, in the same study such correlations were not found in men's group [30].…”
Section: Discussionmentioning
confidence: 76%
“…A striking finding in our study was a significant positive correction between MMI and BMD of the femur and the spine, these results are consistent with a meta-analysis published in 2014 that includes 15,260 women between 18 and 92 years where muscle mass has a positive relation with BMD of the femoral neck, with the data adjusted for age (26). However, there are studies that refute this hypothesis, like a population in China that includes 516 men and 652 older women and no relation between the muscle mass and risk of osteoporosis was found (p = 0.205) (27). There are no local studies that can compare our results.…”
Section: Discussionsupporting
confidence: 90%
“…Such adaptations in physically inactive and sedentary participants may aid in their ability to perform a range of movements with precision and confidence in a variety of scenarios [1]. This can facilitate the improvement of health and fitness, enhance physical performance, reduce the relative risk of injury, and develop confidence and competence [1] in trainees, potentially leading toward reduced mortality [2], cardiovascular disease [3], among other health-markers improvements [4].…”
Section: Discussionmentioning
confidence: 99%
“…Habitual development of these qualities may improve health and fitness, enhance physical performance, reduce the relative risk of injury, and develop confidence and competence [1]. Moreover, poor muscular fitness is associated with mortality [2], cardiovascular disease [3], among other health markers [4], with recent findings demonstrating an alarming trend towards reduced muscular fitness in young population over the years [5], a reduction that showed accelerated rates in recent decades [6].…”
Section: Introductionmentioning
confidence: 99%